On Colonialism, Psychiatric Disorders and the Guyanese Academic: An Interpretation of Jan Lowe Shinebourne’s “Jacob” from The Godmother and Other Stories - Persaud Cheddie, Abigail (Journal of English Language and Literature (ISSN: 2368-2132), 2018)
In this paper, I provide an interpretation of Jan Lowe Shinebourne’s short story “Jacob” by situating it amidst two other similar literary cases and contextualizing it with Frantz Fanon’s ideas about colonialism and psychiatric disorders. I analyse Jacob as a Guyanese academic whose loss of his usual ‘consciousness’, when he comes face-to-face with an academic edifice in England, can be accounted for by the anxieties he developed through having a “colonised personality”. To support this idea, I provide a catalogue of Jacob’s memories and reflections and examine how the workings of these suggest that the most plausible reason for his mental breakdown is the interplay of his academic endeavours and variables of his colonial background.